Strategies of digital marketing at Yamaha Motorcycle Bangladesh and factors contributing to the success of campaigns - Hossain, Kazi Tahmid (Brac University, 2024)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2022.